Strain of Care for Delirium Index: Validity and Reliability - Meltem Ulus; Aylin Durmaz Edeer (Türk Yoğun Bakim Derneği Dergisi)
Objective: Care burden threatens the physical, psychological, emotional, and functional health of caregivers. Caring for patients with delirium leads to stress, increased emotional load and workload in nurses. The strain of care for delirium index (SCDI) was developed to measure the subjective burden of nurse’s experience in the care of patients with delirium. The aim of this study is to examine the Turkish validity and reliability of the " The strain of care for delirium index ". Materials and Methods: This study was conducted in a methodological and cross-sectional type. The sample consisted of 102 nurses working in the intensive care unit for at least 6 months. Results: The goodness-fit indices obtained in the confirmatory factor analysis were at an acceptable level. In the explanatory factor analysis of the scale, factor loads were found to be between 0.343 and 0.865. Item-to- total correlation coefficients ranged from 0.298 to 0.627 and above 0.20 for each item. Conclusion: Reliability refers to consistency between independent measurements of the same thing. In this study, Cronbach's alpha coefficient and item-total correlations were used to measure reliability. In this study, the Cronbach's alpha coefficient was 0.89. Therefore, SCDI has been accepted as a highly reliable measurement tool. In the reliability analysis of the original index, the Cronbach’s alpha coefficient was found to be 0.88. The Turkish version of the SCDI is a valid and reliable scale to evaluate the care difficulty of nurses caring for patients with delirium.